Detection of Plasminogen Activator Inhibitor-1 (PAI-1) mRNA in Human Megakaryocytes by In Situ Hybridization - Alessi, M C; Chomiki, N; Berthier, R; Schweitzer, A; Fossat, C; Juhan-Vague, I (Thrombosis and Haemostasis, 1994)
Platelets have been described to contain a large proportion of the circulating plasminogen activator inhibitor type 1 (PAI-1) which is released on platelet activation. This protein could be taken up by platelets from the plasma or synthesized by megakaryocytes (MKs). Recently, PAI-1 mRNA has been detected in a human megakaryoblastic leukemia cell line (MEG-01) by the polymerase chain reaction (PCR). However, a direct demonstration of its presence in normal human MKs is lacking.In order to prove directly the megakaryocytic origin of platelet PAI-1, the MEG-01 cell line, human bone marrow enriched in MKs, and bone marrow smears from allogeneic bone marrow transplantation donors were investigated for the presence of PAI-1 mRNA using in situ hybridization (ISH). Specimens of bone marrow were first stained with May-Grunwald Giemsa (MGG) for cell identification according to their morphology. Subsequently, the same slides were used for ISH. PAI-1 mRNA was clearly demonstrated in the MEG-01 cell line and in MKs, and its presence correlated with the detection of PAI-1 antigen by immunocytochemistry. PAI-1 mRNA was also detected in morphologically characterized mature granulocytes of marrow samples.